Development-induced displacement and resettlement : causes, consequences, and socio-legal context - Terminski, Bogumil (Ibidem-Verlag, 2015)
This book explores the issue of development-induced resettlement, with a particular emphasis on the humanitarian, legal, and social aspects of this problem. Today, so-called 'development-induced displacement and resettlement' (DIDR) is one of the dominant causes of internal spatial mobility worldwide. Each year over 15 million people are forced to abandon their homes to make space for economic development infrastructure. The construction of dams and irrigation projects, the expansion of communication networks, urbanization and re-urbanization, the extraction and transportation of mineral resources, forced evictions in urban areas, and population redistribution schemes count among the many possible causes. Terminski aims to present the issue of development-caused displacement as a highly diverse, global social problem occurring in all regions of the world. As a human rights issue it poses a challenge to public international law and to institutions providing humanitarian assistance. A significant part of this book is devoted to the current dynamics of development-caused resettlement in Europe, which has been neglected in the academic literature so far.